Tratamento de sementes de milho: avaliações fisiológicas, bioquímicas, de crescimento e da produção - Barbieri, Ana Paula Piccinin (2014)
The aim of this study was to evaluate the effect of growth regulator products in seed treatment, on the physiological potential and biochemical activity at normal conditions and drought; the physiological potential in salt stress; the growth models; and the field performance and productivity of maize hybrids. Thus, different experiments were conducted in the laboratory and an experimental field area using maize hybrids (30F53H and CD393) and the products: gibberellic acid, Stimulate® and thiamethoxam. In general, the effect of the products on the function of plant growth regulator in the seed treatment varies according to the hybrid and the environmental conditions. Gibberellic acid and Stimulate promote an increase on germination rate in both normal and stressed conditions. All products acted beneficially on the seeding establishment of maize in the field. Treatment with thiamethoxam and Stimulate allow faster growth rates. However, the observed differences in vigor and growth are not reflected in higher productivity. Moreover, superoxide dismutase and guaiacol peroxidase do not result the improved performance of plants under water deficit, when treated with growth regulator products.